The integration of knowledge management in the operations of Malaysian banks - Muhamad Ali, Hafizi; Ahmad, Nor Hayati (Universiti Utara Malaysia, 2006)
The globalization of financial markets forced bankers to be knowledge-based and be more efficient in managing knowledge in their banking operations. The importance of this function is accentuated further by the call from the Central Bank of Malaysia (Bank Negara Malaysia) to integrate the concepts of knowledge management in banking operations. In this paper, we discuss a research model called: Banking Knowledge Management Model (BKMM),which encompasses knowledge creation, knowledge retention and knowledge sharing and more importantly, how each of these elements can be integrated to enhance the quality of banking operations. The various components of BKMM are explained and we illustrate the application of BKMM in two Malaysian commercial banks. We find that the two banks apply the concept of knowledge management in line with BKMM but differ in their knowledge management approach. Despite different approach, both banks derive many benefits from applying knowledge management in their operations. We expect a wider application of BKMM by other banks in Malaysia would create a culture that promote and enhance knowledge management in the banking sector.